Performance of Soybean Crop under Tree Species. - Sharma, S.K.; Chauhan, Sanjeev K. (Indian Journal of Agroforestry, 2020)
The experiments on soybean and tree species interactions was laid out in split plot design, keeping tree species (plum, toot and daru) and direction (East and West) in the main plot, and distances (1, 2 and 3m) of data recording in sub-plot, The performance of soybean crop under three tree species was uniform. The growth and yield attributes however, recorded lower values under shade in comparison to open conditions. The number of grains per pod and 100 grain weight under shade of these species and open were statistically at par. The crop yield decreased in the close proximity with the trees and significantly increased with the increase in distance from the trees during both years of study. Data recorded on crop parameters from two directions during first year of study did not exhibit significant differences, however, during second year values were higher on western side than on eastern side of the plants.